2012
DOI: 10.1007/s11854-012-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Absolutely continuous spectrum for random operators on trees of finite cone type

Abstract: We study the spectrum of random operators on a large class of trees. These trees have finitely many cone types and they can be constructed by a substitution rule. The random operators are perturbations of Laplace type operators either by random potentials or by random hopping terms, i.e., perturbations of the off-diagonal elements. We prove stability of arbitrary large parts of the absolutely continuous spectrum for sufficiently small but extensive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…A new proof was found in [24], and it was later shown in [6,7] that spectral delocalization and ballistic transport hold in larger regions of the spectrum. Similar results were obtained for more general tree models in [31,25]. One reason that makes trees technically simpler to analyze is the fact that the Green function on a tree satisfies some convenient recursion and factorization relations.…”
Section: Introductionsupporting
confidence: 75%
“…A new proof was found in [24], and it was later shown in [6,7] that spectral delocalization and ballistic transport hold in larger regions of the spectrum. Similar results were obtained for more general tree models in [31,25]. One reason that makes trees technically simpler to analyze is the fact that the Green function on a tree satisfies some convenient recursion and factorization relations.…”
Section: Introductionsupporting
confidence: 75%
“…In this case, the spectrum is purely absolutely continuous. In fact, the authors in [18] establish more generally that the absolutely continuous spectrum of A remains stable under small radially symmetric perturbations H = A + λV , if the tree is non-regular. Large parts of the absolutely continuous spectrum also remain stable under small random perturbations H ω = A+λV ω ; see [19].…”
Section: Introductionmentioning
confidence: 99%
“…For small disorder in the bulk of the spectrum, localization and Poisson statistics appears in one and quasione dimensional systems [GMP, KuS, CKM, Lac, KLS] (except if prevented by a symmetry [SS3]) and is expected (but not proved) in 2 dimensions. Delocalization for the Anderson model was first rigorously proved on regular trees (Bethe lattices) [Kl] and had been extended to several infinitedimensional tree-like graphs [Kl,ASW,FHS,AW,KLW,FHH,KS,Sa2,Sa3,Sha]. Recently it was shown that there is a transition from localization to delocalization on normalized antitrees at exactly 2-dimensional growth rate [Sa4].…”
mentioning
confidence: 99%